The China's Economic Interest in Investing in Ethiopia in 2018 - Muhamad Aryabima Pratama (Jurusan Ilmu Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sriwijaya, 2023)
Each country has its own advantages and disadvantages, there are countries that contain a lot of natural resources or countries that have large industrial power. It is on this basis that China, as one of the world's superpowers, wants to expand its market access and obtain more natural resources for the sustainability of its country, therefore China is cooperating with other countries. In this article the author will discuss the method of China's economic interests in investing in Ethiopia, using descriptive qualitative by looking for existing sources and data and focusing on using the theory of national interests, why China chooses countries in the African region, especially Ethiopia . After searching for several sources, the author can conclude that China's economic interests in investing in Ethiopia itself are divided into 2, the first is to make the countries in the African region that work with it become a backup energy source for China itself, and the second itself is to expand the reach international market access